Overview of UK research on the durability of container materials for radioactive wastes. (September 2014) - Padovani, C.
<x content-type="archive" xml:space="preserve">Abstract</x> Radioactive Waste Management Limited (RWM), formerly the Radioactive Waste Management Directorate of the UK Nuclear Decommissioning Authority (NDA RWMD), has a continuing programme of research and development to support the safe disposal of radioactive wastes in a geological disposal facility (GDF). This paper describes the part of RWM's research programme aimed at developing a robust understanding of the durability of container materials for a variety of potential wastes. It includes background information, a summary of relevant past and continuing R&D projects and, to a more limited extent, links to relevant scientific literature produced elsewhere. The paper considers separately the case of intermediate level waste (ILW), for which container materials are better defined, durability requirements are less stringent and the development of the disposal system in the UK is more mature, and that of high level waste (HLW) and spent fuel, for which a broader range of disposal options is being considered, durability requirements are more stringent and information available in the UK is currently largely based on international developments.